Design for living [videorecording (DVD)] - Lubitsch, Ernst, 1892-1947; Lubitsch, Ernst, 1892-1947; March, Fredric, 1897-1975; Cooper, Gary, 1901-1961; Hopkins, Miriam, 1902-1972; Horton, Edward Everett (Criterion collection, 2011)
A trio of Americans in Paris who enter into a very adult 'gentleman's' agreement, in this continental pre-Code comedy freely adapted by Ben Hecht (Notorious) from a play. A risque relationship comedy and a witty take on creative pursuits, it concerns a commercial artist unable, or unwilling, to choose between the equally dashing painter and playwright she meets on a train en route to the City of Light.